2019
DOI: 10.1002/ppul.24327
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical characteristics of severe Mycoplasma pneumoniae pneumonia in children

Abstract: Objectives: To analyze the molecular and the clinical characteristics of Mycoplasma pneumoniae (Mp) pneumonia (MPP) and to explore the related factors predicting severe MPP (SMPP).Methods: A total of 423 pediatric cases of MPP were retrospectively analyzed, in 2013-2017, in Beijing, China. Clinical information was collected from the medical records. Mp-positive specimens were characterized using P1 typing and multiple locus variable-number tandem repeat analysis (MLVA). The macrolide resistanceassociated mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
47
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 36 publications
8
47
2
Order By: Relevance
“…Patients with severe MPP had significantly increased levels of neutrophils, CRP and PCT, as well as reduced levels of lymphocytes and platelets compared to patients with general MPP. These findings are consistent Yan et al [8,16,17]. Previous studies have suggested that thrombocytopenia is an extrapulmonary manifestation of MPP [3,18].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Patients with severe MPP had significantly increased levels of neutrophils, CRP and PCT, as well as reduced levels of lymphocytes and platelets compared to patients with general MPP. These findings are consistent Yan et al [8,16,17]. Previous studies have suggested that thrombocytopenia is an extrapulmonary manifestation of MPP [3,18].…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the patients with severe MPP had a fever lasting more than 7 days, a cough lasting more than 2 weeks, and most required hospitalization for more than 7 days. Patients with general MPP had significantly shorter fever durations, cough durations, and hospitalizations compared to those with severe MPP, consistent with previous reports [8,14,15]. The Japanese Respiratory Society's scoring system provides guidance for recognizing MPP, with white blood cell (WBC) count < 10 × 10 9 /L being one of six standard parameters [3].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…5,6 MP is one of the predominant causative agents of pneumonia in children, in addition to the respiratory infection system, MP contributes to a broad array of extrapulmonary diseases, some of which can be even life-threatening. 7,8 A better understanding of the prevalence of RTIs in children is essential for implementing an effective approach for prevention, control, and treatment, because of lacking vaccines for most of these respiratory pathogens, especially MP.…”
mentioning
confidence: 99%
“…At present, there are few studies on MPP with hypoxia. However, the current theory of excessive immune response causing MPP disease progression is generally accepted [20][21][22][23] . In the laboratory indicators, the level of WBC, neutrophil ratio, CRP, LDH, IL-6 and ferritin were related to MPP with hypoxia, which was similar to the previous case reports [24][25][26] .…”
Section: Discussionmentioning
confidence: 99%